Thermische Alterung von Dieseloxidationskatalysatoren und NOx-Speicherkatalysatoren: Korrelierung von Aktivität und Speicherfähigkeit mit physikalischen und chemischen Katalysatoreigenschaften - Chan, Denise (KIT Scientific Publishing, 2013)
Increasing demands on emission limitations caused by legislative directives call for numerical simulation to support the development of automotive exhaust gas aftertreatment systems. Since the efficiency in pollution abatement of automotive converters decreases over the technical lifetime, the aging behavior has to be considered when designing aftertreatment systems. The objective of this work is a better understanding of thermal aging of diesel oxidation catalysts and NOx trap catalysts.